2a(a+1)-3(a+1)=0

Simple and best practice solution for 2a(a+1)-3(a+1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2a(a+1)-3(a+1)=0 equation:


Simplifying
2a(a + 1) + -3(a + 1) = 0

Reorder the terms:
2a(1 + a) + -3(a + 1) = 0
(1 * 2a + a * 2a) + -3(a + 1) = 0
(2a + 2a2) + -3(a + 1) = 0

Reorder the terms:
2a + 2a2 + -3(1 + a) = 0
2a + 2a2 + (1 * -3 + a * -3) = 0
2a + 2a2 + (-3 + -3a) = 0

Reorder the terms:
-3 + 2a + -3a + 2a2 = 0

Combine like terms: 2a + -3a = -1a
-3 + -1a + 2a2 = 0

Solving
-3 + -1a + 2a2 = 0

Solving for variable 'a'.

Factor a trinomial.
(-1 + -1a)(3 + -2a) = 0

Subproblem 1

Set the factor '(-1 + -1a)' equal to zero and attempt to solve: Simplifying -1 + -1a = 0 Solving -1 + -1a = 0 Move all terms containing a to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1a = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1a = 0 + 1 -1a = 0 + 1 Combine like terms: 0 + 1 = 1 -1a = 1 Divide each side by '-1'. a = -1 Simplifying a = -1

Subproblem 2

Set the factor '(3 + -2a)' equal to zero and attempt to solve: Simplifying 3 + -2a = 0 Solving 3 + -2a = 0 Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2a = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2a = 0 + -3 -2a = 0 + -3 Combine like terms: 0 + -3 = -3 -2a = -3 Divide each side by '-2'. a = 1.5 Simplifying a = 1.5

Solution

a = {-1, 1.5}

See similar equations:

| 5x-5/(x-1)(x-1) | | -4x+1=-9 | | 1m=9 | | 5/2+7/8 | | 13+3/4x=28 | | 64-4j=j+9 | | -17x^2+51x=0 | | (5x-5)/(x-1)(x-1) | | 64-4j=j+10 | | -19=m-28 | | 4.2=0.8k | | x(21x+13)+2=0 | | K^2=5k-6 | | 60/6+38= | | 2(x+-1)=12 | | 6m+25=9m-2 | | 7(2x-4)=-196 | | -5+5+10= | | 5m=70 | | 5b-15=2b+15 | | 3x-2+3x=40 | | 8x+-8=6x+7 | | c/0.2=-1.6 | | -1/2z=3/4-1/4 | | 5x+17-4x=-8-13 | | -109+9x=164-12x | | (u+1/2)-(u-1/49)=1 | | -25+50+6= | | c^4-1296= | | x/3+4=x/2+8 | | 3x/10-1/2=x/5 | | 0.25(4r+-8)=r-2 |

Equations solver categories